“I THINK, SHE DOES NOT KNOW THIS ANY MORE”: CHILD AGENCY NEGOTIATED THROUGH THE DYNAMICS OF FAMILY INTERACTIONS IN GERMANY DURING COVID-19 - Berner-Rodoreda, Astrid; Baum, Nina; Ganten, Maria-Katharina; Hoegl, Henriette; Zangerl, Kathrin; Bärnighausen, Till (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2025)
We examined child agency in terms of prevailing theories of childhood (seeing children as “been”, “being”, or “becoming”) in the context of interviews about COVID-19 experiences. In our study we focused on conversations between the interlocutor (a child or a parent) and additional family members and used a discourse approach for analyzing and interpreting the interactions. In total, 9 families of diverse sociocultural backgrounds (13 parents and 16 children aged 6–15 years) were interviewed about their individual COVID-19 experience in Germany. Irrespective of age, children were able to describe events and experiences during COVID-19 times and were thus aware of the “been”. These ranged from enjoying playtime with parents to playgrounds being cordoned off and classmates being ill. Interview interactions underscored a dynamic of children’s agency that alternated between active involvement in their own and the parent’s interview and reactively referring questions to a parent or letting the parent take control of the interview situation. Neither parents’ views of children nor children’s own behavior could be consistently assigned to the category of “being” or “becoming”. Rather, our study highlighted children’s agency along a being–becoming continuum through an interactive transformational process in terms of interdependent agency between children and parents in a particular context. This process of negotiated agency should be explored further in future studies with children and parents.